Precipitação eletrostática de nanopartículas: desenvolvimento de metodologias e investigações de fenômenos - Oliveira, Alessandro Estarque de (2019)
Mitigation of atmospheric pollutants emission and recovery of high-added value products are the main goals of studies on the optimization of devices that collect nanoparticles, which harmfulness is reported in the scientific literature. In the meantime, electrostatic precipitators collect above 99.9% of the particulate in a wide size range. However, studies on nanoparticles have evaluated velocities used in the industrial scale, while velocities less than 10 cm/s are barely explored. It is known that this range of velocities influences positively the diffusional mechanism in the filtration of nanoparticles. In order to evaluate this range of gas velocities, this work used a wire-plate electrostatic precipitator composed of two grounded copper plates with 30 cm of length, 10 cm of height, and 4.0 cm of spacing, and containing 8 stainless steel wires in its longitudinal axis, with diameter of 0.30 mm and 4.0 cm of spacing. Nano-aerosols of KCl, Fe2O3, NiO, and NaCl (this latter was only used in initial tests) were produced by the atomization of solutions and suspensions by nano-aerosols atomizers. Increase of particle concentration and decrease of gas velocity increased the efficiency in tests with two values of gas velocities (3.3 and 6.6 cm/s), each with two values of KCl solution concentrations (0.4 and 2.0 g/L), as well as in tests with 0.2, 0.4, and 2.0 g/L at 3.3 cm/s and tests with 1.0, 2.5, and 5.0 g/L at 8.2 cm/s, all under -8.0 kV. A methodology was purposed in which the aqueous concentration was varied proportionally with the gas velocity, using KCl aqueous concentrations of 4.0, 5.0, and 6.0 g/L respectively to 6.6, 8.2, and 9.9 cm/s, under -8.0 kV, in order to mitigate the dilution effect. Experimental results showed that it was possible to isolate the residence time effect on the efficiency. With this new methodology, tests were performed to evaluate velocities of 1.7, 3.3, 6.6, 9.9, 14.8, and 19.9 cm/s, using KCl solutions respectively of 0.5, 1.0, 2.0, 3.0, 4.5, and 6.0 g/L and electric fields of 3.95, 4.00, and 4.10 kV/cm. Electric field influenced positively the efficiency. Maximum points of efficiency were observed for 6.6 cm/s, which is not reported in the literature for nanoparticles and was associated with residence time, electro-fluid dynamics and diffusional effects of the particles. In tests with nanoparticles of NiO and Fe2O3 at 3.3 cm/s, it was verified the production of nanoparticles with narrower size distributions in the outlet of the device in relation to its inlet from -8.5 kV. This phenomenon was promoted by decreasing the velocity – evaluated in 1.61, 3.23, 4.83, 3.3, and 9.9 cm/s – and increasing the voltage – evaluated in -8.0, -8.5, -9.0, -10.0, -11.0, -13.0, and -15.0 kV – and was associated with the disaggregation of oxide agglomerates and the erosion of the wires. Finally, efficiency models coupled with Stokes Law and the Li and Wang model for the drag force were compared with experimental data. The efficiency model of Li-Chen-Tsai coupled with Li and Wang model better fitted the experimental data.